2016
DOI: 10.3102/0002831215627857
|View full text |Cite
|
Sign up to set email alerts
|

Undermatched? School-Based Linguistic Status, College Going, and the Immigrant Advantage

Abstract: Considerable research investigates the immigrant advantage, yet little work examines the influence of school-based linguistic status. Contradictory patterns exist: research identifies both an immigrant advantage and a language minority disadvantage in college going. Although not all immigrant youth are language minorities, many do speak a language other than English. Educators in U.S. schools group immigrant students into three discrete linguistic categories: native English speakers, language minorities not in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 108 publications
(141 reference statements)
1
47
0
Order By: Relevance
“…Numerous studies have encountered more successful postsecondary outcomes among Latinas relative to their male counterparts (Riegle-Crumb, 2010;Saenz & Ponjuan, 2009). Further, Hispanic students whose first language is not English may find it more challenging to access four-year institutions, at least in part due to inadequate academic preparation (Callahan & Humphries, 2016;Gándara & Contreras, 2009). Parent resources including income and level of education are also widely recognized influences on Hispanic students' college enrollment (Kim & Díaz, 2013;Nora & Crisp, 2009;Nuñez & Kim, 2012;O'Connor et al, 2010;Perna & Titus, 2005).…”
Section: Student and Family Backgroundmentioning
confidence: 99%
“…Numerous studies have encountered more successful postsecondary outcomes among Latinas relative to their male counterparts (Riegle-Crumb, 2010;Saenz & Ponjuan, 2009). Further, Hispanic students whose first language is not English may find it more challenging to access four-year institutions, at least in part due to inadequate academic preparation (Callahan & Humphries, 2016;Gándara & Contreras, 2009). Parent resources including income and level of education are also widely recognized influences on Hispanic students' college enrollment (Kim & Díaz, 2013;Nora & Crisp, 2009;Nuñez & Kim, 2012;O'Connor et al, 2010;Perna & Titus, 2005).…”
Section: Student and Family Backgroundmentioning
confidence: 99%
“…Regarding higher education, research finds that students who were EL-classified in K-12 are less likely to graduate high school, enroll in college, and complete college as compared to their non-EL peers, although outcomes vary widely and are strongly correlated with reclassification timing (Kanno & Cromley, 2013;Nuñez & Sparks, 2012). Students who attain English proficiency early on (and those who enter kindergarten already proficient in both their home language and English) often have strong academic profiles (Kieffer & Thompson, 2018;Saunders & Marcelletti, 2013) and are likely to attend college (Callahan & Humphries, 2016). However, students who retain EL status into the middle school years, and those who enter U.S. schools at the secondary level, are less likely to successfully complete college preparatory coursework and go to college, compared to their non-EL peers (Jaquet & Fong, 2017).…”
Section: Policy Area #9: Pre-k Through Postsecondary Education Alignmentmentioning
confidence: 99%
“…One study by Kanno and Cromley (2013) showed that students who retained EL classification in eighth grade were half as likely as non-EL language minority students to earn a bachelor's degree. Additionally, students who graduate high school classified as EL tend to enter less selective schools -such as community colleges -compared to their non-EL peers (Callahan & Humphries, 2016), and even academically high-performing ELs face numerous barriers to college entry (Kanno, 2018). Other research shows that, among relatively high-performing EL students, not exiting EL status in high school directly reduces students' likelihood of enrolling in college (Carlson & Knowles, 2016).…”
Section: Policy Area #9: Pre-k Through Postsecondary Education Alignmentmentioning
confidence: 99%
“…Using national data, they found that ELs advanced to post-secondary institutions at a much lower rate and that ELs were overrepresented in "no post-secondary institutions" while underrepresented in "four-year institutions" (Kanno & Cromley, 2013). This suggests that high-achieving ELs tend to be over prepared for the post-secondary options in which they enroll (Callahan & Humphries, 2016).…”
Section: Policies and Proceduresmentioning
confidence: 99%
“…The high repetition rates of Algebra I among EL students is concerning (Jacquet & Fong, 2017). As ELs are developing proficiency in English, access to rigorous courses in math is critical, along with ongoing sufficient support in language development to succeed in those courses (Callahan & Humphries, 2016;Jaquet & Fong, 2017;Mosqueda, 2010). Research on math placement in the middle school grades determined that students enrolled in algebra, honors math, or an elective math course in grades sixth through eighth had significantly higher test scores on a standardized assessment compared to students enrolled in standard math courses (Wang & Goldschmidt, 1999).…”
Section: Math As a Gatekeepermentioning
confidence: 99%